RETRACTED: N-TERMINAL PRO-BRAIN NATRIURETIC PEPTIDE (NT-proBNP) IN STAGE 1 AND STAGE 2 HYPERTENSION PATIENTS - Supriati Wila Djami (Indonesian Journal of Medical Laboratory Science and Technology, 2019)
This article has been retracted at the request of the Editor in Chief of the Indonesian Journal of Medical Laboratoy Science and Technology (IJMLST) volume 1 number 2 of 2019 pages 65-73 with DOI: 10.33086/ijmlst.v1i2.1159 because it has been published in the Journal of Health Information volume 17 number 1 year 2019 pages 64-74 with DOI: 10.31965/infokes.Vol17.Iss1.232.